Князі стародубські та рильські: середина XIV – початок XV століть - Келембет, С. (Сiверянський лiтопис, 2015)
У статті пропонується нова версія походження першого князя Стародубського у складі Великого князівства Литовського – Патрикія Давидовича. Зібрано та проаналізовано всі відомості, що збереглися у джерелах про цього князя, а також його синів та онуків. В статье предлагается новая версия происхождения первого князя Стародубского в составе Великого княжества Литовского – Патрикия Давидовича. Собраны и проанализированы все сведения, которые сохранились в источниках об этом князе, а также его сыновьях и внуках. The First Starodubskyi Prince in the Grand Lithuania Duchy was Patrykiy Davydovych who, in this title, was known only by its record in Lyubetskiy sinodik and pomyannik of Vedenska Kiyevo-Percherska Lavra church. In the historiography this prince,usually was identified Patrykiy Narymuntovych, grandson of Grand Lithuania Duke, Gediminas. Narimunt had a Christian name of Glib, which was considered as a synonym of the name David as one of the first ancient Holy Prince Glib Volodymyrovych, in baptism was called David. However, nowadays it is proved that in the pre-Mongol period names Glib and David began to be used separately, each as princely, and christening. In sources of different types, at that time the most ancient pomyannik of the Kiyevo-Percherska Lavra, Narimunt appears with a name Glib, and his brother was called as Yuriy Glibovych. So Patrykiy Narimuntovych- Glibovych had no relation to Patrykiy Davydovych Starodubskyi. The Prince Patrykiy who was Keystut Gediminovich deputy in Horodne is repeatedly mentioned in sources of the Teutonic Order during 1350- the 1360th years, and in 1365 received new possession «in Russian land». In Polish historiography he was identified with Patrykiy Keystutovych (mythical), then with Patrykiy Narimuntovych. In fact there are good arguments in favor of this Prince who was identical to Patryckiy Davydovych. Prince David as his father can be recognized the commander Gedymin, and also the Governor Horodenskyi. After removal from the Horodne Patryckii Davydovych, a vassal of Keystut, got the siverskyi Starodub. That was in conformity with the agreement between the Grand Duke Olgerd and Keystut that all newly acquired land, and thus Siverschyna, they will be shared with each other in half. The second part of the aricle are collects and analyses all the information having preserved in the sources about Patrykyi Davydovych’s sons and grandsons Princes Starodubskyi and Rylskyi. More over, on the bottom of Vedenska Kiyevo-Pecherskaya Lavra Church monument it is established the existence of the previously unknown Prince Starodubskyi – Fedor Oleksandrovych, Patrykyi’s grandson.